2016
DOI: 10.1097/md.0000000000003965
|View full text |Cite
|
Sign up to set email alerts
|

Does public reporting influence antibiotic and injection prescribing to all patients? A cluster-randomized matched-pair trial in china

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 40 publications
(62 reference statements)
0
41
0
Order By: Relevance
“…Inappropriate use of antibiotics is influenced by nonbiomedical factors within and beyond clinical settings that are unique to mainland China, yet common among lowincome and middle-income countries, including public misconceptions, 16-18 22 28 31 35 36 43 57 59 habitual use without professional guidance, 58 insufficient FDA monitoring, 56 incentivising the healthcare system towards prescribing and selling, 23 24 56 lack of diagnostic capacity, 25 27 and the delicate relationships between patients and prescribers, 27 but some critical factors such as antibiotic literacy remained as research gaps. To date, there have been only few interventions implemented in primary care settings to reduce inappropriate prescribing, [64][65][66][67][68][69][70] largely targeting clinicians and ignoring demand-side factors. Further, more research is needed to investigate the associations between human and animal use of antibiotics in rural China, where 564 million people reside 71 in order to inform effective One Health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate use of antibiotics is influenced by nonbiomedical factors within and beyond clinical settings that are unique to mainland China, yet common among lowincome and middle-income countries, including public misconceptions, 16-18 22 28 31 35 36 43 57 59 habitual use without professional guidance, 58 insufficient FDA monitoring, 56 incentivising the healthcare system towards prescribing and selling, 23 24 56 lack of diagnostic capacity, 25 27 and the delicate relationships between patients and prescribers, 27 but some critical factors such as antibiotic literacy remained as research gaps. To date, there have been only few interventions implemented in primary care settings to reduce inappropriate prescribing, [64][65][66][67][68][69][70] largely targeting clinicians and ignoring demand-side factors. Further, more research is needed to investigate the associations between human and animal use of antibiotics in rural China, where 564 million people reside 71 in order to inform effective One Health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Hubei had 347 UCHCs and 1137 RTHCs, receiving 23.03 million and 56.00 million outpatient visits, respectively [26]. Over-prescription of antibiotics was prevalent in these facilities: 65% of prescriptions contained antibiotics and 20% involved two or more antibiotics [27].…”
Section: Methodsmentioning
confidence: 99%
“…Public opinion/expectations and peer comparison appear to influence prescribing behaviours but in contrasting ways depending on the disease, patient cohort and doctor’s ranking. Liu et al [58], Tang et al [59], Tang et al [60], and Yang et al [61] reported effects of public reporting in primary care settings in China. Data on antibiotic prescribing (percentage of prescriptions including antibiotics or injections, and cost) were collected and individual doctors and facilities were compared and rankings were published publicly, e.g., on posters outside facilities.…”
Section: Table A1mentioning
confidence: 99%